TINJAUAN YURIDIS TERHADAP PEMBANGUNAN PERUMAHAN OLEH PERUSAHAAN PENGEMBANG YANG BELUM MEMILIKI IZIN MENDIRIKAN BANGUNAN DI KOTA SAMARINDA - Sudirman Sudirman (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Building conservation permit is the most fundamental thing to be considered by the developer of housing, before doing development activities. Building permit is also a tool or means of control Pemerinth in conducting supervision of any development, so that in the arrangement of the City can be arranged neatly.This study aims to determine the causes of housing developers in building housing although not yet have a building permit. The efforts of the regional government in the framework of the issuance of housing development, and the effort to build the building permit by the developer due to the weakness of the supervision of the licensing agency, the lack of coordination among relevant licensing agencies, and the legal awareness of developers and consumers is still low. Strikes and sanctions and socialization of licensing rules.